2019
DOI: 10.1111/jdv.15300
|View full text |Cite
|
Sign up to set email alerts
|

Validation of ‘ItchApp©’ in Poland and in the USA: multicentre validation study of an electronical diary for the assessment of pruritus

Abstract: Background Although chronic pruritus affects a large part of the population, its reliable assessment remains difficult. Electronical diaries (eDiaries) are often used in multicentre clinical trials. The ItchApp© for Android was developed to assess itch intensity and course and was validated for the German language in 2017. Objective To validate ItchApp© for the use in the Polish and US English languages. Methods Fifty‐three subjects in Poland and thirty subjects in the USA with chronic pruritus completed the p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 18 publications
1
3
0
Order By: Relevance
“…In another psychometric analysis, an ICC of 0.78 was noted for WI-NRS in patients with PN . Consistently, excellent reliability (ICC, 0.99) for WI-NRS has also been demonstrated in patients with chronic prurigo . Furthermore, the results of this study were in line with the ICC values reported for other PROs in patients with chronic itch (ICC between 0.74 and 0.87) …”
Section: Discussionsupporting
confidence: 89%
“…In another psychometric analysis, an ICC of 0.78 was noted for WI-NRS in patients with PN . Consistently, excellent reliability (ICC, 0.99) for WI-NRS has also been demonstrated in patients with chronic prurigo . Furthermore, the results of this study were in line with the ICC values reported for other PROs in patients with chronic itch (ICC between 0.74 and 0.87) …”
Section: Discussionsupporting
confidence: 89%
“…The “ItchApp©” is like an e-Diary for the assessment of pruritus and has been validated in English, Polish, and German. [ 24 ]…”
Section: Classificationmentioning
confidence: 99%
“…WI‐NRS does not attempt to take into account itch duration or the variability that is often experienced throughout the day and night by patients with chronic itch. The 24‐h average itch NRS (AI‐NRS) attempts to integrate the peaks and valleys of itch severity throughout a 24‐h period into a singular score 5. Our study aims to determine correlations between WI‐NRS and AI‐NRS and to determine the influence of itch duration on these measures.…”
Section: Worst Itch Nrs Average Itch Nrs Mean ± Sd Difference From ≥ mentioning
confidence: 99%